2010
DOI: 10.1021/jf102063q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Thermophilic l-Rhamnose Isomerase from Thermoanaerobacterium saccharolyticum NTOU1

Abstract: L-rhamnose isomerase (EC 5.3.1.14, L-RhI) catalyzes the reversible aldose-ketose isomerization between L-rhamnose and L-rhamnulose. In this study, the L-Rhi gene encoding L-Rhi was PCR-cloned from Thermoanaerobacterium saccharolyticum NTOU1 and then expressed in Escherichia coli. A high yield of the active L-RhI, 9780 U/g of wet cells, was obtained in the presence of 0.2 mM IPTG induction. L-RhI was purified sequentially using heat treatment, nucleic acid precipitation, and anion-exchange chromatography. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
(58 reference statements)
2
35
0
Order By: Relevance
“…The similar result was reported on another metal-dependent enzyme, Geobacillus stearothermophilus L-arabinose isomerase, which also displayed null activity without metal ions, but rapidly restored catalytic activity by adding trace amount of Mn 2+ [23]. Interestingly, for aldose isomerase or ketose epimerase having metal coordinating region in structure, some enzyme are metal-dependent and must require metal cofactor to display activity [15], [23], [24]; some not only do not require metal ions but also could not be activated by metal ions [20], [25], [26]; and other could display catalytic activity without metal ion, however, their activity could be remarkably enhanced by metal ions [13], [14], [16]. The mechanism of different metal independence of these enzymes having metal coordinating region may be fascinating topic worthy of deep investigation.…”
Section: Resultssupporting
confidence: 79%
“…The similar result was reported on another metal-dependent enzyme, Geobacillus stearothermophilus L-arabinose isomerase, which also displayed null activity without metal ions, but rapidly restored catalytic activity by adding trace amount of Mn 2+ [23]. Interestingly, for aldose isomerase or ketose epimerase having metal coordinating region in structure, some enzyme are metal-dependent and must require metal cofactor to display activity [15], [23], [24]; some not only do not require metal ions but also could not be activated by metal ions [20], [25], [26]; and other could display catalytic activity without metal ion, however, their activity could be remarkably enhanced by metal ions [13], [14], [16]. The mechanism of different metal independence of these enzymes having metal coordinating region may be fascinating topic worthy of deep investigation.…”
Section: Resultssupporting
confidence: 79%
“…All of the identified L‐RIs are metal‐dependent enzymes, and these L‐RIs are significantly activated by Co 2+ or Mn 2+ . Interestingly, only in T. saccharolyticum NTOU1 and C. saccharolyticus ATCC 43494 L‐RIs was Co 2+ shown to be the optimum metal cofactor among the reported L‐RIs. The presence of Co 2+ or Mn 2+ has also been showed to apparently improve the activity of other aldose isomerases and ketose epimerases.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, many studies have focused on L‐RIs because they have broad substrate specificity and show great potential for producing various rare sugars. So far, L‐RIs have been isolated and characterized from Escherichia coli , Pseudomonas stutzeri , Bacillus pallidus Y25, Thermoanaerobacterium saccharolyticum NTOU1, Thermotoga maritima ATCC 43589, Caldicellulosiruptor saccharolyticus ATCC 43494, Mesorhizobium loti Tono, Bacillus halodurans ATCC BAA‐125, Dictyoglomus turgidum DSMZ 6724, Bacillus subtilis ATCC 23857, Bacillus subtilis str. 168 and Thermobacillus composti KWC4 .…”
Section: Introductionmentioning
confidence: 99%
“…The purified enzyme could be activated by Mn Leang et al, 2004b. b Poonperm et al, 2007. c Lin et al, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…The alignment of L-RhIs from different species revealed that B. subtilis L-RhI shares 76.42% identity with that from B. halodurans (Prabbu et al, 2011), 57.28% identity with L-RhI from E. coli K12, 56.47% identity with L-RhI from B. pallidus Y25 (Poonperm et al, 2007), 55.45% identity with L-RhI from T. saccharolyticum NTOU1 (Lin et al, 2010), but only 18.30% identity with L-RhI from P. stutzeri (Table 3). So far, crystal structures of L-RhIs from E. coli and P. stuzeris have been resolved, of which the structure of E. coli L-RhI and its relationship with xylose isomerase was the first report (Korndörfer et al, 2000).…”
Section: Comparison With L-rhis From Other Organismsmentioning
confidence: 99%